Cancer Biomarkers in Body Fluids - Bianchi, Fabrizio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Liquid biopsy shows promise for cancer screening and diagnostics. This reprint collects recent scientific literature on the identification and application of tumor biomarkers in biological fluids to improve the diagnosis of cancer and the identification of optimal therapeutic strategies.